STACKING SEQUENCE OPTIMISATION OF COMPOSITE PANELS SUBJECTED TO SLAMMING IMPACT LOADS USING A GENETIC ALGORITHM - KHEDMATI, MOHAMMAD REZA (2013)
<!-- /* FONT DEFINITIONS */ @FONT-FACE {FONT-FAMILY:"CAMBRIA MATH"; PANOSE-1:2 4 5 3 5 4 6 3 2 4; MSO-FONT-CHARSET:0; MSO-GENERIC-FONT-FAMILY:ROMAN; MSO-FONT-PITCH:VARIABLE; MSO-FONT-SIGNATURE:-536870145 1107305727 0 0 415 0;} @FONT-FACE {FONT-FAMILY:NAZANIN; PANOSE-1:0 0 4 0 0 0 0 0 0 0; MSO-FONT-CHARSET:178; MSO-GENERIC-FONT-FAMILY:AUTO; MSO-FONT-PITCH:VARIABLE; MSO-FONT-SIGNATURE:8193 0 0 0 64 0;} /* STYLE DEFINITIONS */ P.MSONORMAL, LI.MSONORMAL, DIV.MSONORMAL {MSO-STYLE-UNHIDE:NO; MSO-STYLE-QFORMAT:YES; MSO-STYLE-PARENT:""; MARGIN:0IN; MARGIN-BOTTOM:.0001PT; TEXT-ALIGN:RIGHT; MSO-PAGINATION:WIDOW-ORPHAN; DIRECTION:RTL; UNICODE-BIDI:EMBED; FONT-SIZE:12.0PT; FONT-FAMILY:"TIMES NEW ROMAN","SERIF"; MSO-FAREAST-FONT-FAMILY:"TIMES NEW ROMAN"; MSO-ANSI-LANGUAGE:EN-GB; MSO-BIDI-LANGUAGE:FA;} .MSOCHPDEFAULT {MSO-STYLE-TYPE:EXPORT-ONLY; MSO-DEFAULT-PROPS:YES; FONT-SIZE:10.0PT; MSO-ANSI-FONT-SIZE:10.0PT; MSO-BIDI-FONT-SIZE:10.0PT;} @PAGE SECTION1 {SIZE:8.5IN 11.0IN; MARGIN:1.0IN 1.0IN 1.0IN 1.0IN; MSO-HEADER-MARGIN:.5IN; MSO-FOOTER-MARGIN:.5IN; MSO-PAPER-SOURCE:0;} DIV.SECTION1 {PAGE:SECTION1;} --> OPTIMISATION OF STACKING SEQUENCE FOR COMPOSITE PANELS UNDER SLAMMING IMPACT LOADS USING A GENETIC ALGORITHM METHOD IS STUDIED IN THIS PAPER. FOR THIS PURPOSE, SLAMMING LOAD IS ASSUMED TO HAVE A UNIFORM DISTRIBUTION WITH A TRIANGULAR-PULSE TYPE OF INTENSITY FUNCTION. IN ORDER TO PERFORM OPTIMISATION BASED ON A GENETIC ALGORITHM, A SPECIAL CODE IS WRITTEN IN MATLAB SOFTWARE ENVIRONMENT. THE PREPARED CODE IS SO COUPLED WITH THE COMMERCIAL SOFTWARE ANSYS IN AN ESPECIAL PROCEDURE THAT IN EACH STEP OF OPTIMISATION, IT COULD ANALYSE THE COMPOSITE PANEL UNDER STUDY AND CALCULATE THE CENTRAL DEFLECTION. AFTER VALIDATION, DIFFERENT CASES OF STACKING SEQUENCE OPTIMISATION ARE INVESTIGATED FOR A VARIETY OF COMPOSITE PANELS. THE INVESTIGATIONS INCLUDE SYMMETRIC AS WELL AS ASYMMETRIC CONDITIONS OF STACKING SEQUENCE. RESULTS OBTAINED FROM THESE ANALYSES REVEAL THE FACT THAT THE ADOPTED APPROACH BASED ON A GENETIC ALGORITHM IS HIGHLY CAPABLE FOR PERFORMING SUCH OPTIMISATIONS.